Anti-acetylcholinesterase, antidiabetic, anti-inflammatory, antityrosinase and antixanthine oxidase activities of Moroccan propolis - EL-GEUNDOUZ, Soukaina (2016)
Biological properties of Moroccan propolis have been scarcely studied. In the present work, the total phenols and flavonoids from 21 samples of propolis collected in different places of Morocco or 3 supplied in the market were determined, as well as the invitro capacity for inhibiting the activities of acetylcholinesterase, -glucosidase, -amylase, lipoxygenase, tyrosinase, xanthine oxidase and hyaluronidase. The results showed that samples 1 (region Fez-Boulemane, Sefrou city) (IC50=0.065, 0.006, 0.020, 0.050, 0.014mgmL(-1)) and 23 (marketed) (IC50=0.018, 0.002, 0.046, 0.037, 0.008mgmL(-1)) had the best invitro capacity for inhibiting the -amylase, -glucosidase, lipoxygenase, tyrosinase and xanthine oxidase activities, respectively. A negative correlation between IC50 values and concentration of phenols, flavones and flavanones was found. These activities corresponded to the generally higher amounts of phenols and flavonoids. In the same region, propolis samples have dissimilar phenol content and enzyme inhibitory activities.